A multifaceted intervention: no increase in general practitioners' competence to diagnose skin cancer (minSKIN) – randomized controlled trial. (10th December 2014) - Badertscher, N.; Tandjung, R.; Senn, O.; Kofmehl, R.; Held, U.; Rosemann, T.; Hofbauer, G.F.L.; Wensing, M.; Rossi, P.O.; Braun, R.P.
Abstract Background General practitioners (GPs) play crucial roles in early detection of skin cancer. A pilot‐study found a positive short‐term effect of a 1‐day dermatologic education programme on GPs' diagnostic competence. Objective To determine effects of a multifaceted intervention, including technical equipment and continuing feedback by a dermatologist, on GPs' diagnostic skills regarding skin cancer. Methods Randomized controlled trial with 78 GPs of the Canton of Zurich, Switzerland. Intervention: GPs in intervention group received a 1‐day training, a Lumio© (magnifying glass with polarized light, 3Gen), a Nikon digital camera and – during 1 year – feedback on skin lesion pictures sent to the dermatologist. GPs in control group only received the 1‐day training. Main outcome and measures: Primary outcome: structured assessment of GP's diagnostic skills in correctly diagnosing images of skin lesions regarding skin cancer. At baseline prior to intervention (T0), after the full‐day training course in both groups (T1), and after 1 year of continuing feedback (T2) to the intervention group. Measures: Non‐parametric unpaired (Wilcoxon–Mann–Whitney) tests were used to compare numbers of correctly classified skin lesions between both groups at T2 and for the change between T1 and T2. Results At T0, both groups classified a median of 23 skin lesions of the 36 images correctly. This value rose to 28 for both groups at T1 and fell to 24 for both groups at T2. No difference between control and intervention group at T2. Furthermore, we compared differences in the sum scores per GP between T1 and T2 for each group. Also in this comparison, no difference between control and intervention group was found. Conclusion and relevance No long‐term effect of the multifaceted intervention was found on the competence to diagnose skin cancer by GPs. The positive short‐term effect of the 1‐day dermatologic education programme did not persist over 12 months.